Respuesta :
Answer:
-2x^3 + 2x^(1/2)
Step-by-step explanation:
step one- plug in the values of each in f(x) - g(x)
x^(1/2)-x - (2x^3-×^(1/2)-x) ; g(x) is in parentheses bc we need to distribute the negative
x^(1/2)-x-2x^3 + x^(1/2) + x ; combine like terms (letters with the same exponents) ; the x's cancel, and the x^(1/2) + x^(1/2) combine to form 2x^(1/2); the -2x^3 remains
you should get
-2x^3 + 2x^(1/2)
Answer:
[tex]f(x) - g(x) = 2(\sqrt{x}-x^3)[/tex]
Step-by-step explanation:
We have the functions
[tex]f(x)= x^{\frac{1}{2}}-x[/tex] and [tex]g(x) = 2x^3-x^\frac{1}{2}-x[/tex]
The operation [tex]f (x) -g (x)[/tex] is the subtraction of the function f(x) minus the function g(x). Thus
[tex]f(x) - g(x) = x^{\frac{1}{2}}-x -(2x^3-x^\frac{1}{2}-x)[/tex]
Simplifying the expression we have left that:
[tex]f(x) - g(x) = x^{\frac{1}{2}}-x -2x^3+x^\frac{1}{2}+x[/tex]
[tex]f(x) - g(x) = 2x^{\frac{1}{2}}-2x^3[/tex]
[tex]f(x) - g(x) = 2(\sqrt{x}-x^3)[/tex] Because [tex]x^{\frac{a}{n}} = \sqrt[n]{x^a}[/tex]